从词义的角度分析新加坡用语者对汉英触碰类动词的日常语码混用习惯 = A study of Singaporeans' chinese-english code-mixing in their everyday uses of touch action verbs from the lexical perspective - 区兆伦 Au, Siu Lun (2013)
语码混用的谈话习惯在新加坡几乎是无所不在，不少研究认为是用语者的词汇量不足，但我们不难发现用语者在日常生活中能够灵活地进行语码转换，更知道标准的表达是什么，而用语者却仍然说话语码混用。本文以语义解构方法分析新加坡用语者语码混用的现象，研究对象是用语者对触碰类手部动作近义词的使用方式，结合语义特征分析以及问卷调查，以解释双语的词汇习得以及语码混用和动词的语义特征的关系，务求从另一个观点解释新加坡用语者在词汇上的区域变体以及语码混用的现象。Code-mixing in speech is a habit of most Singaporeans. While many researchers suggest that this is due to the fact that speakers have insufficient vocabularies, it is not difficult to find instances, in which Singaporeans speakers are able to efficiently switch between two languages to communicate in daily life, and these speakers chose to code-mix despite knowing the standard expressions. This paper attempts to analyze the code-mixing habits of Singaporeans by semantic decomposition, focusing on their uses of touch action verbs in daily life. This research uses a combination of semantic feature analysis and questionnaires data analysis in attempt to explain the relationship between bilingual acquisition of vocabularies, code-mixing, and semantic features of vocabularies. This might be able to provide an explanation to the geological variations of lexicon in Singapore and the code mixing phenomenon from another perspective.